Pengaruh Model Pembelajaran Role-Playing terhadap Keterampilan Berbicara Siswa Kelas IV MIN 4 Kota Medan - Nurul Hidayah Hasibuan; Riris Nurkholidah Rambe; Muhammad Syaifullah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Difficulties in speaking include students being able to convey messages well but still using their mother tongue, being embarrassed and nervous about speaking in front of the class and even forgetting what they are going to convey. Role-playing is an effective learning model in improving students' speaking skills. This model can help students become more active, independent and happy during the learning stage. This research aims to determine the effect of the role-playing learning model on students' speaking skills. By applying a quantitative approach and quasi-experimental design, this research involved a population of 112 students. The research sample consisted of 59 students, where class IV A as the experimental class included 31 students and class IV B as the control class consisted of 28 students. The instrument used in this research is a non-test technique in the form of a performance test. Hypothesis testing is carried out using the t test after first carrying out a normality test. The results of the significance value (2-tailed) of 0.001 < 0.05 indicate that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.